REPRESENTASI NILAI KEARIFAN LOKAL DALAM FILM BERBAHASA JAWA BERJUDUL TURAH - Oktavia, Nisa; Susanto, Gatut (Hiski Malang, 2023)
Electronic mass media is a very efficient tool in disseminating information. Electronic mass media is widely used by the public because it is faster than other media. Films, which are a category of electronic mass media, are often a means of providing entertainment and are used to build certain discourses for society. It is not uncommon for genres in films to present local wisdom of certain regions. Local wisdom contains guidelines for determining actions and deeds that will be implemented every day. The film Turah is a film that presents the local wisdom of the coastal community of Kampung Tirang. Based on the explanation above, the aim of this research is to describe the value of local wisdom and the presentation of local wisdom values ​​in films. This type of research is descriptive qualitative. The results of data analysis found that there are 5 values ​​of local wisdom in the film Turah, namely, wisdom in livelihood, wisdom in language, wisdom in social relationships, wisdom in relationships with God, and wisdom in real form. The value of local wisdom is presented verbally and also visually. By presenting local wisdom in a film, it will open people's awareness that these values ​​need to be preserved. Local wisdom needs to be maintained to maintain community identity and balance the environment and nature, because currently people lack awareness regarding the true essence of local wisdom.